Accuracy and reliability of digital craniofacial measurements using a small‐format, handheld 3D camera - Kim, A. J.; Gu, D.; Chandiramani, R.; Linjawi, I.; Deutsch, I. C. K.; Allareddy, V.; Masoud, M. I. (Orthodontics & craniofacial research, 2018)
Structured Objectives Craniofacial assessments often involve three‐dimensional facial imaging using an expensive camera with 6 SLR lenses to analyse the positions and relations of anatomic landmarks. Recently, a 3D small‐format, handheld camera was developed; however, the accuracy and reliability of this system are largely unknown. The purpose of this study was to evaluate the accuracy and reliability of this system. Materials & Methods A total of 30 sets of evaluations were completed by 2 examiners on 5 human subjects, using 3 different methods: direct callipers, 3D handheld camera and conventional tripod 3D camera images. Each evaluation included 29 anthropometric landmarks that were used as reference points for facial analysis. Two examiners marked the landmarks directly on the faces and measured linear distances using the 3 measurement methods. Results Accuracy analysis was performed for handheld vs direct calliper vs conventional camera measurements. Each of these analyses yielded a grand mean of correlation coefficients of .98. Bias measurements revealed that the handheld and conventional camera methods yielded larger measurements than direct callipers (with a mean difference of 1.74, 1.56 mm, respectively, for rater 1 and 0.94, 1.02 mm, respectively, for rater 2). When compared to one another, both the handheld camera and the conventional camera methods yielded similar values for most measurements, with the average overall difference between these modalities of 0.03 mm for rater 1 and 0.07 mm for rater 2. Conclusions The 3D handheld camera showed high accuracy and reliability in comparison with traditional models, indicating that this system may provide a useful tool in craniofacial anthropometry.